How Customer Success Managers Operationalise Segmentation Strategies in B2B SaaS Companies - Espíndola Michel, José Alejandro (My University, 2025)
This thesis investigates how Customer Success Managers (CSMs) leverage customer segmentation strategies to prioritize client engagement and allocate resources in mid-sized B2B Software-as-a-Service (SaaS) companies. While segmentation is a foundational concept in strategic marketing, its operational implementation by CSMs in resource-constrained environments remains underexplored. The central research question guiding this study is: How do CSMs leverage customer segmentation strategies to prioritize client engagement and allocate resources in mid-sized B2B SaaS companies? To address this gap, the study adopts a qualitative, interpretivist, single-case embedded design. Drawing on segmentation theory (Payne & Frow, 2005), Customer Lifetime Value (Kumar & Reinartz, 2016), and resource allocation models (Reinartz et al., 2004), twelve semi-structured interviews with CSMs were conducted and analysed using thematic analysis (Braun & Clarke, 2006). The findings reveal that segmentation frameworks are often ambiguously defined and inconsistently applied. CSMs interpret and adapt segmentation logic based on client behaviour, internal pressures, and resource limitations. Formal segmentation is used as a starting point but frequently adjusted through practitioner discretion. Key challenges include informal re segmentation, role ambiguity, misalignment with Account Executives, and inadequate system integration. Automation supports scaled engagement for low-tier clients but creates friction when client expectations are mismatched. This study contributes to strategic marketing literature by demonstrating that segmentation is not only a top-down planning tool but also an interpretive and negotiated practice. It offers actionable guidance for SaaS leaders seeking to embed dynamic, context-sensitive segmentation frameworks into Customer Success operations and to align resource prioritization with customer value across the lifecycle.
Keywords: marketing; customers; customer relationship management; customer segmentation; business management; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business